GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE EVIDENCE FROM MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN (2015-2020) - Arifin, Bustanul; Dhestriani Mulyahati Adam, Thaesha (Review of Accounting and Taxation, 2024)
Purpose - This research aims to examine the influence of Green Accounting and Corporate Social Responsibility on financial performance. The sample in this research is 26 companies listed on the Indonesia Stock Exchange for the 2015-2020 period Design/methodology/approach - Purpose Sampling method. The data used in this research is secondary data obtained from the Company's financial reports and annual reports have been published on the official website of the Indonesia Stock Exchange (IDX) (www.idx.co.id) during the 2015-2020 period. This research uses multiple linear regression analysis. The data in this research is processed using SPSS software (Statistical Product and Service Solution) version 23. Finding - The results of this research show that Green Accounting has no effect on financial performance and Corporate Social Responsibility (CSR) has a significant negative effect on financial performance. Originality -